O direito fundamental à herança: âmbito de proteção e consequências de sua constitucionalização - Gomes, Felipe Lima (2015)
The paper investigates the inclusion of the right to inheritance in the Brazilian Constitution of 1988 and its consequences to the compatibilization of infraconstitutional rules related to hereditary rights. In the first two chapters, the concepts concerning the theory of fundamental rights that are necessary to the issue are specified. Rober Alexy’s theory on principles, for whom the fundamental rights’ norms have, generally, the nature of a optimization command, is adopted as the theoretical reference to the explanation of the fundamental right’s norms' nature and of how they could collide. Further, it is analyzed the concepts of restriction and scope of protection of fundamental rights, in order to trace the legal situations that concern the right to inheritance. In the third chapter, a few fundamental structures of the Brazilian Law of Successions are analyzed, regarding both lawful and testamentary succession, establishing important notions to the ongoing of the research. In the last part, the effects of constitutionalisation of the right to inheritance are told, which gives them the specific treatment of a fundamental right. As a result, a few hereditary rights’ problems are chosen, which are reinterpreted according to the constitutional treatment of fundamental right that was given to the right to inheritance.